PROPUESTA METODOLÓGICA DE APRENDIZAJE Y TRANSFERENCIA DE CONOCIMIENTO DE LOS TESOROS NATURALES Y CIENTÍFICOS DEL YASUNÍ, PARA LOS ESTUDIANTES DE LA CARRERA DE CIENCIAS SOCIALES. - Estrada Gaibor, Cristian Geovanny (2020)
The Methodological proposal for Learning and Transfer of Knowledge of the Natural and Scientific Treasures of Yasuní, for Students of the Social Sciences career, is a current investigation in the national and international context due to this sector of the country. The research problem was the weak knowledge of the Natural and Scientific Treasures of Yasuní; for this reason, the research aims to disseminate the methodological proposal for learnin gand knowledge transfer, the same as through the methodological guide "Sistema of Geographic Information” (GIS) will serve as a starting point for the students. The learning theories that support the research are social constructivism, based on Vygotsky's Socio-Historical-Cultural learning and Ausubel's significant learning; likewise, the methodology is quantitative-qualitative with a non-experimental research design. Through a survey that was applied to students in the fourth and fifth semester before the research to be carried out, the following results were obtained: 47.7% and 48.8%. Thus, when applying the “GIS” proposal, a level of knowledge could be identified obtaining 73.3% and 68% regarding of Natural and Scientific Treasures' socialization. This appreciation allows us to conclude that the proposal related to the Natural and Scientific Treasures of Yasuní contributed to the knowledge and strengthening of learning. However, the use of ICTs with applications such as “GIS” is recommended, which are pedagogical strategies for localization and analysis.